Situation analysis of rehabilitation services for persons with disabilities in Bangladesh: identifying service gaps and scopes for improvement. Issue 19 (11th September 2022) - Al Imam, Mahmudul Hassan; Jahan, Israt; Das, Manik Chandra; Muhit, Mohammad; Akbar, Delwar; Badawi, Nadia; Khandaker, Gulam
Abstract: Purpose: Rehabilitation needs are rising globally; however, the rate is strikingly higher in low- and middle-income countries (LMICs). Like many LMICs, the situation of rehabilitation services for persons with disabilities (PwDs) in Bangladesh is mostly unknown. We assessed the current situation of rehabilitation services for PwDs in Bangladesh. Materials and methods: This mixed-method study incorporated an online survey of rehabilitation service providers and a scoping review of documents published on rehabilitation services for PwDs in Bangladesh. Descriptive and thematic analyses were completed. Results: A total of 1102 rehabilitation service providers were interviewed, and 36 documents were reviewed. Rehabilitation services for PwDs were found not integrated into the mainstream health services, financing mechanisms, information systems, and health policies in Bangladesh. There are 6.8 rehabilitation units for 1 million people, and 6.2% of them are located in rural areas. In terms of the rehabilitation workforce, there are 9.4 physiotherapists, 1.3 occupational therapists, 0.9 speech and language therapists, and 0.2 prosthetist and orthotists for 1 million people in Bangladesh. Majority (66.3%) of rehabilitation services require an out-of-pocket payment. Conclusions: A critical shortage and uneven distribution of the rehabilitation workforce are evident, indicating a likelihood of very high unmet rehabilitation needs in Bangladesh. To strengthen the rehabilitation capacity of Bangladesh, rehabilitation services should be integrated into mainstream health policies and programs with a special focus on the rehabilitation workforce training, recruitment and distribution, and allocation of resources. Implications for rehabilitation: Rehabilitation services in Bangladesh are mostly provided by the private sector, although the government of Bangladesh operates a small number of rehabilitation services outside of the mainstream public health service delivery system. Rehabilitation services are lacking in the primary and secondary health facilities, while services at tertiary level public hospitals are mainly provided by medical technologists in the absence of a qualified rehabilitation workforce. A severe shortage of rehabilitation workforce coupled with an uneven distribution of the existing limited number of rehabilitation services and out-of-pocket expenditures might result in inadequate access and poor rehabilitation service uptake amongst persons with disabilities (PwDs) in Bangladesh. Robust governance and leadership are needed to monitor the implementation of existing legislations and policies and develop strategies to improve the situation of rehabilitation services for PwDs in Bangladesh.